Method for preparing PET (Polyethylene Terephthalate) copolyester in short process
Through short-process alcoholylation and polycondensation reaction, waste PET polyester is prepared into PET copolyester using ethylene glycol and titanium bimetallic catalysts, solving the problems of complex PET recycling technology and high energy consumption, and achieving rapid and effective PET recycling.
Patent Information
- Application Number
- CN202411714575.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The existing PET recycling technology is complex, has long processes, high energy consumption, and requires multiple processing and catalyst addition, which limits recycling efficiency and environmental protection performance.
The use of a short process method is used to mix the waste PET polyester with ethylene glycol and titanium bimetallic catalyst, perform alcoholylation reaction and accurately control the reaction end point, and directly carry out polycondensation reaction to prepare PET copolyester without additional catalyst supplementation or separation and esterification steps in the middle.
It realizes the rapid and efficient recycling of PET waste, simplifies the process flow, reduces energy consumption, reduces the use of metal elements, and improves the recycling efficiency and the molecular weight distribution of the product.
Smart Images

Figure BDA0005156611810000031 
Figure BDA0005156611810000032 
Figure BDA0005156611810000042
Abstract
Description
Technical Field
[0001] The present invention relates to the field of recycling of waste materials, and more specifically, to a method for preparing PET copolyester by a short process. Background Art
[0002] Polyethylene terephthalate (PET) is a widely used thermoplastic polyester material. Due to its good mechanical properties, heat resistance and chemical stability, it is often used in beverage bottles, food packaging and textiles. However, the widespread use of PET has also brought significant environmental problems, especially the accumulation of waste caused by its non-degradability. Therefore, it is crucial to develop effective PET recycling technology. At present, PET recycling methods are mainly divided into physical recycling and chemical recycling. Physical recycling regenerates PET materials through processes such as washing, crushing and melting, but its recycling effect is limited by the purity of the raw materials and the impurity content. Chemical recycling converts waste PET into its raw material monomers through chemical reactions, which can efficiently process complex and mixed PET wastes and improve recycling efficiency.
[0003] Chemical recycling technologies include different methods such as hydrolysis, alcoholysis and pyrolysis. The hydrolysis method decomposes PET into terephthalic acid and ethylene glycol by reacting with water under high temperature and pressure. The alcoholysis method uses alcohols (such as methanol, ethanol, and ethylene glycol) to react with PET to produce alcohol esters and monomers. The pyrolysis method decomposes PET into low molecular weight compounds through high temperature treatment in an oxygen-deficient or oxygen-free environment. These methods can not only effectively recycle waste PET, but also produce high-purity raw monomers to meet higher standards of application requirements. Compared with physical recycling, the advantages of chemical recycling are its higher recovery rate, tolerance to pollutants, and the possibility of closed-loop recycling, which plays a positive role in reducing the environmental burden.
[0004] The patent with publication number CN118374057A discloses a method for preparing PET copolyester by alcoholysis and polymerization of waste PET, but different catalysts need to be used in the alcoholysis and polymerization stages, and stabilizers and antioxidants need to be added to the polymerization system, which is complicated to operate. The patent with publication number CN112441917A discloses a method for recovering terephthalate by transesterification reaction of waste PET and alkyl alcohol, but the product needs to be processed in multiple steps, the process is complicated, and the energy consumption is high. Therefore, a simpler method is needed to recycle PET. Summary of the invention
[0005] Based on the above problems, an object of the present invention is to provide a method for preparing PET copolyester in a short process. The method can directly use the alcoholysis reaction product to carry out polycondensation reaction to prepare PET copolyester by selecting a suitable alcoholysis agent and catalyst and accurately controlling the reaction end point of the alcoholysis reaction, without the need to supplement any materials such as catalyst in the middle, and without any separation step and esterification step. The method is simple to operate, uses less catalyst, has a short process route, and has low energy consumption, thereby realizing the recycling of waste PET polyester.
[0006] Another object of the present invention is to provide a PET copolyester.
[0007] In order to achieve the above first object, the present invention adopts the following technical scheme:
[0008] The present invention discloses a method for preparing PET copolyester from waste PET polyester, comprising the following steps:
[0009] Waste PET polyester, alcoholysis agent and catalyst are mixed, and alcoholysis reaction is carried out in a closed reactor. The reaction is stopped when the number average molecular weight of the oligomer obtained by the alcoholysis reaction is controlled to be 5000-7000 g / mol and the degree of polymerization is 25-35. Then, the polycondensation reaction is completed under high vacuum conditions to obtain PET copolyester.
[0010] Furthermore, the alcoholysis agent is selected from ethylene glycol; the catalyst is selected from one or more of antimony catalysts, germanium catalysts, rare earth catalysts, and titanium catalysts, preferably a titanium bimetallic catalyst. The preparation method of the titanium bimetallic catalyst is prepared with reference to CN108034046A. The titanium bimetallic catalyst selected in the present invention can catalyze the alcoholysis of PET polyester and the synthesis of copolyester, and is a high-efficiency catalyst with dual catalytic effects.
[0011] Furthermore, the amount of the alcoholysis agent used is 0.5-10 times the mass of the waste PET polyester.
[0012] Further, the amount of the catalyst is 0.01-0.5% of the mass of the waste PET polyester. Exemplarily, the amount of the catalyst can also be 0.01-0.1%, 0.01-0.2%, 0.01-0.3%, 0.01-0.4%, 0.05-0.1%, 0.05-0.2%, 0.05-0.3%, 0.05-0.4%, 0.05-0.5%, 0.1-0.2%, 0.1-0.3%, 0.1-0.4%, 0.1-0.5%, 0.2-0.3%, 0.2-0.4%, 0.2-0.5%, 0.3-0.4%, 0.3-0.5%, 0.4-0.5%, etc. of the mass of the waste PET polyester.
[0013] Furthermore, the reaction temperature of the alcoholysis reaction is 180-230° C., and the reaction time of the alcoholysis reaction is 1.0-8.0 h.
[0014] Furthermore, the reaction temperature of the polycondensation reaction is 240-260° C., and the reaction time of the polycondensation reaction is 0.5-5.0 h.
[0015] Furthermore, the vacuum degree in the polycondensation reaction is controlled at 10-100 Pa.
[0016] Furthermore, the waste PET polyester is selected from one or more of waste PET bottles, waste PET films and waste PET fibers, and has a number average molecular weight of 10-40 kg / mol.
[0017] In order to achieve the above second purpose, the present invention adopts the following technical solutions:
[0018] The invention discloses PET copolyester prepared by the method as described above.
[0019] The beneficial effects of the present invention are as follows:
[0020] The invention provides a method for preparing PET copolyester by utilizing waste PET polyester quickly and effectively. The method comprises the following steps: the waste PET polyester is subjected to alcoholysis reaction under the action of alcoholysis agent ethylene glycol and a catalyst (such as a titanium-based bimetallic catalyst); the alcoholysis reaction is accurately controlled by regulating the reaction temperature and the reaction time; the obtained oligomer is in a state of having a number average molecular weight of 5000-7000 g / mol and a degree of polymerization of 25-35; and the alcoholysis reaction product is directly subjected to polycondensation reaction to prepare the PET copolyester, thereby realizing the recycling of PET waste.
[0021] After the alcoholysis reaction is completed, the system does not need any separation step, and the esterification stage can be skipped to directly carry out the polycondensation reaction. The oligomer after alcoholysis has moderate fluidity in the melt state, which is not too high to limit the subsequent end groups from colliding with each other to produce the polycondensation reaction, and ensures that the product has a good molecular weight distribution; at the same time, it is not too low to consume too much energy, which can greatly simplify the process flow and shorten the time cost.
[0022] The catalyst selected in the present invention (such as a titanium-based bimetallic catalyst) can catalyze both alcoholysis of PET polyester and synthesis of copolyester, so that the reaction system can successfully transition from alcoholysis reaction to polycondensation reaction without adding a polycondensation catalyst for a second time in the entire method. At the same time, since the amount of catalyst used in the alcoholysis reaction is relatively small and no new catalyst needs to be added in the subsequent polycondensation reaction, the low metal element content in the recovered polymer is guaranteed.
[0023] The waste PET polyester selected in the present invention has a wide range of sources, and can be waste PET bottles, waste PET films, waste PET fibers, etc. The method realizes the recycling of PET waste into polymer products. DETAILED DESCRIPTION
[0024] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the content described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0025] The molecular weight and distribution of the polymer were tested by gel permeation chromatography (GPC, e2695, Waters, USA), with chloroform and o-chlorophenol as a mixed solvent, chloroform as the mobile phase, and PMMA as the reference substance.
[0026] The content of metal elements in the polymer was measured using an inductively coupled plasma mass spectrometer (ICP-MS-2030, Shimadzu, Japan) with trifluoroacetic acid as the solvent.
[0027] The titanium-based bimetallic catalyst used in the following specific examples of the present invention is prepared according to the preparation conditions of Example 1 in CN108034046A.
[0028] Examples 1-11
[0029] Waste PET polyester alcoholysis and polymerization to prepare PET copolyester, the steps are as follows:
[0030] (1) Alcoholysis: Waste PET polyester (100.0 g), ethylene glycol (300.0 g) and a certain amount of titanium bimetallic catalyst were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath pot equipped with a mechanical stirrer. The stirring speed was 300 rpm. After reacting at a certain temperature for a certain time, an oligomer with a number average molecular weight of about 5000-7000 g / mol and a degree of polymerization of 25-35 was obtained.
[0031] (2) Polymerization: Use an oil pump to reduce the pressure of the reaction system to below 100 Pa, increase the stirring speed to 450 rpm, and carry out polycondensation at a certain temperature. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PET copolyester is obtained.
[0032] In Examples 1-11, the amount of catalyst used, alcoholysis temperature, alcoholysis time, molecular weight of oligomer, polycondensation temperature and polycondensation time in each example are shown in Table 1, and the molecular weight of PET copolyester obtained in each example is shown in Table 2.
[0033] Table 1. Reaction parameters in Examples 1-11
[0034]
[0035] Table 2. Molecular weight of PET copolyesters in Examples 1-11
[0036]
[0037]
[0038] Comparative Example 1
[0039] The preparation of PET copolyester by alcoholysis and polymerization of waste PET polyester is different from that in Example 7 in that the reaction time is prolonged to completely hydrolyze the PET polyester into monomers, and then the polymerization reaction is carried out, and the steps are as follows:
[0040] (1) Alcoholysis: Waste PET (100.0 g), ethylene glycol (300.0 g) and titanium bimetallic catalyst (0.15 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath equipped with a mechanical stirrer. The reaction temperature was controlled to be 200°C, the stirring speed was 300 rpm, and after 6.0 h of reaction, the yield of the monomer product bis(hydroxyethyl) terephthalate was 80.1%.
[0041] (2) Polymerization: Under normal pressure, the esterification reaction was carried out at 200-240°C for 180 minutes, and the stirring speed was 450 rpm. Then, the pressure of the reaction system was reduced to below 100 Pa by an oil pump, and the polycondensation reaction was carried out at 250°C. The polycondensation reaction lasted for about 60 minutes. When the viscosity of the polymer increased significantly and the torque of the stirring device reached 30 N·cm, the reaction was considered to have reached the end point, and PET copolyester was obtained.
[0042] Comparative Example 2
[0043] The PET copolyester was prepared by alcoholysis and polymerization of waste PET polyester, which is different from Comparative Example 1 in that the PET polyester was hydrolyzed into oligomers with a molecular weight of about 2000 g / mol, and then the polymerization reaction was carried out, and the steps were as follows:
[0044] (1) Alcoholysis: Waste PET (100.0 g), ethylene glycol (300.0 g) and titanium bimetallic catalyst (0.15 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath equipped with a mechanical stirrer. The reaction temperature was controlled at 200 °C and the stirring speed was 300 rpm. After reacting for 3.0 h, an oligomer with a number average molecular weight of about 2000 g / mol was obtained.
[0045] (2) Polymerization: Use an oil pump to reduce the pressure of the reaction system to below 100 Pa, raise the temperature of the oil bath to 250°C, and increase the stirring speed to 450 rpm to carry out polycondensation. The polycondensation reaction lasts for about 80 minutes. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PET copolyester is obtained.
[0046] Comparative Example 3
[0047] The PET copolyester was prepared by alcoholysis and polymerization of waste PET polyester, which is different from Comparative Example 1 in that the PET polyester was hydrolyzed into oligomers with a molecular weight of about 10,000 g / mol, and then the polymerization reaction was carried out, and the steps were as follows:
[0048] (1) Alcoholysis: Waste PET (100.0 g), ethylene glycol (300.0 g) and titanium bimetallic catalyst (0.15 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath equipped with a mechanical stirrer. The reaction temperature was controlled at 200 °C and the stirring speed was 300 rpm. After reacting for 1.5 h, an oligomer with a number average molecular weight of about 10,000 g / mol was obtained.
[0049] (2) Polymerization: Use an oil pump to reduce the pressure of the reaction system to below 100 Pa, raise the temperature of the oil bath to 250°C, and increase the stirring speed to 450 rpm to carry out polycondensation. The polycondensation reaction lasts for about 60 minutes. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PET copolyester is obtained.
[0050] The reaction parameters and product conditions in Example 7 and Comparative Examples 1-3 are shown in Table 3.
[0051] Table 3. Reaction parameters and product conditions in Example 7 and Comparative Examples 1-3
[0052]
[0053] By comparison, it can be found that the alcoholysis and polymerization time will be greatly prolonged if the polyester is depolymerized into monomers or oligomers with lower molecular weight and then polymerized. When the alcoholysis time is shortened to obtain oligomers with larger molecular weight, the viscosity of the oligomer is high, which affects the normal progress of the polycondensation reaction and causes the molecular weight distribution of the copolyester to become wider.
[0054] Comparative Example 4
[0055] The waste PET polyester alcoholysis and polymerization to prepare PET copolyester is different from Example 7 in that the catalyst used in the reaction is tetrabutyl titanate, and the steps are as follows:
[0056] (1) Alcoholysis: Waste PET (100.0 g), ethylene glycol (300.0 g) and tetrabutyl titanate (0.19 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath equipped with a mechanical stirrer. The reaction temperature was controlled at 200 °C and the stirring speed was 300 rpm. After reacting for 4.0 h, an oligomer with a number average molecular weight of about 6000 g / mol was obtained.
[0057] (2) Polymerization: Use an oil pump to reduce the pressure of the reaction system to below 100 Pa, raise the temperature of the oil bath to 250°C, and increase the stirring speed to 450 rpm to carry out polycondensation. The polycondensation reaction lasts for about 110 minutes. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PET copolyester is obtained.
[0058] Comparative Example 5
[0059] PETG copolyester was prepared by alcoholysis and polymerization of waste PET polyester, which was different from Comparative Example 4 in that the amount of tetrabutyl titanate was different, and the steps were as follows:
[0060] (1) Alcoholysis: Waste PET (100.0 g), ethylene glycol (300.0 g) and tetrabutyl titanate (0.32 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath equipped with a mechanical stirrer. The reaction temperature was controlled at 200 °C and the stirring speed was 300 rpm. After reacting for 2.0 h, an oligomer with a number average molecular weight of about 6000 g / mol was obtained.
[0061] (2) Polymerization: Use an oil pump to reduce the pressure of the reaction system to below 100 Pa, raise the temperature of the oil bath to 250°C, and increase the stirring speed to 450 rpm to carry out polycondensation. The polycondensation reaction lasts for about 70 minutes. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PET copolyester is obtained.
[0062] Comparative Example 6
[0063] PETG copolyester was prepared by alcoholysis and polymerization of waste PET polyester. The difference from comparison 5 is that tetrabutyl titanate was added twice in the alcoholysis reaction and polymerization. The steps are as follows:
[0064] (1) Alcoholysis: Waste PET (100.0 g), ethylene glycol (300.0 g) and tetrabutyl titanate (0.16 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath equipped with a mechanical stirrer. The reaction temperature was controlled at 200 °C and the stirring speed was 300 rpm. After reacting for 4.5 h, an oligomer with a number average molecular weight of about 6000 g / mol was obtained.
[0065] (2) Polymerization: Tetrabutyl titanate (0.16 g) was added to the three-necked flask, the pressure of the reaction system was reduced to below 100 Pa using an oil pump, the temperature of the oil bath was raised to 250°C, the stirring speed was increased to 450 rpm, and the polycondensation reaction was carried out. The polycondensation reaction lasted for about 70 minutes. When the viscosity of the polymer increased significantly and the torque of the stirring device reached 30 N·cm, the reaction was considered to have reached the end point, and PET copolyester was obtained.
[0066] In Example 7 and Comparative Examples 4-6, the reaction parameters and product conditions are shown in Table 4.
[0067] Table 4. Reaction parameters and product conditions in Example 7 and Comparative Examples 4-6
[0068]
[0069] By comparison, it can be found that when tetrabutyl titanate is used as a catalyst, the reaction efficiency is relatively low compared to titanium-based bimetallic catalysts, and a longer alcoholysis time or more catalysts are required to obtain a copolyester equivalent to that in the example. However, increasing the amount of catalyst may lead to a higher content of metal elements in the prepared copolyester.
[0070] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing PET copolyester by a short process, characterized in that: The steps include: Waste PET polyester, alcoholysis agent and catalyst are mixed, and alcoholysis reaction is carried out in a closed reactor. The reaction is stopped when the number average molecular weight of the oligomer obtained by the alcoholysis reaction is controlled to be 5000-7000 g / mol and the degree of polymerization is 25-35. Then, the polycondensation reaction is completed under high vacuum conditions to obtain PET copolyester.
2. The method according to claim 1, characterized in that The alcoholysis agent is selected from ethylene glycol; the catalyst is selected from one or more of antimony catalysts, germanium catalysts, rare earth catalysts, and titanium catalysts.
3. The method according to claim 1, characterized in that The catalyst is selected from titanium-based bimetallic catalysts.
4. The method according to claim 1, characterized in that: The amount of the alcoholysis agent used is 0.5-10 times the mass of the waste PET polyester.
5. The method according to claim 1, characterized in that The dosage of the catalyst is 0.01-0.5% of the mass of the waste PET polyester.
6. The method according to claim 1, characterized in that The reaction temperature of the alcoholysis reaction is 180-230° C., and the reaction time of the alcoholysis reaction is 1.0-8.0 h.
7. The method according to claim 1, characterized in that The reaction temperature of the polycondensation reaction is 240-260° C., and the reaction time of the polycondensation reaction is 0.5-5.0 h.
8. The method according to claim 1, characterized in that The vacuum degree in the polycondensation reaction is controlled at 10-100 Pa.
9. The method according to claim 1, characterized in that: The waste PET polyester is selected from one or more of waste PET bottles, waste PET films and waste PET fibers, and has a number average molecular weight of 10-40 kg / mol.
10. PET copolyester, characterized in that The method is prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Efficient polyester composite catalyst and preparation method and application thereof
CN108034046A
Method for recovering terephthalate from waste PET
CN112441917A
Method for alcoholysis of waste PET and preparation of PET copolyester
CN118374057A
Preparation method of recycled polyester
CN104327254A
Method for preparing PETG / PCTG copolyester by depolymerizing waste PET with mixed alcohol
CN115490839A